Barriers to the implementation of virtual care programmes for patients with chronic wounds: Qualitative empirical research - Nasib Babaei; Vahid Zamanzadeh; Leila Valizadeh; Mojgan Lotfi; Ahmad Kousha; Taha Samad‐Soltani; Marziyeh Avazeh (Wiley, 2023)
Abstract Aim To assess the barriers to the implementation of virtual care for patients with chronic wounds from wound therapists' perspective. Design A qualitative study. Methods The study was conducted in two consecutive phases: (1) literature review, (2) descriptive qualitative study. In the first phase, texts published in English until 2023 were identified using international databases. The entire text of the selected studies was evaluated independently by two reviewers. Data analysis was carried out using textual content analysis. In the second phase of the study, twelve participants from Iranian wound care clinics participated. Data were collected through focus group discussion and analysed using conventional content analysis. Integration of both phases was conducted in the data analysis stage. Results The most important barriers in providing virtual care to patients with chronic wounds were identified into five categories including lack of policymaking in virtual care, ethical challenges in virtual information and communication technology, social, economic and cultural issues, IT users' insufficient knowledge and limitation of virtual care scope of practice. Conclusion The findings of the present study identified different barriers in the implementation of virtual care for patients with chronic wounds. In order to successfully develop a virtual care programme, it is necessary to adopt suitable policies regarding information and communication technology, provide the necessary legal frameworks, assign an adequate budget and consider the ethical, cultural, social and social issues. Implications for the Profession and/or Patient Care Identifying barriers to developing a virtual care programme will help manage patients with chronic wounds at home. Impact This study accurately identifies barriers to providing virtual care for patients with chronic wounds and helps plan to address these barriers and facilitate the development of a virtual care programme for these patients at home. Reporting Method This research has adhered to the SRQR reporting guideline. No Patient or Public Contribution The involvement of patients or the public in the design, or conduct, or reporting, or dissemination plans of this research was not suitable.